Gel polymer electrolyte and preparation method thereof, lithium metal battery and electronic product
By using a specific proportion of polymers and aliphatic dinitrile solvents in lithium metal batteries, the problems of lithium dendrites growth and electrolyte decomposition are solved, the conductivity and stability of the battery are improved, and the performance of the battery is achieved. Improved electrochemical performance and safety.
Patent Information
- Application Number
- CN202411045664.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-13
Smart Images

Figure CN119133585A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a gel polymer electrolyte and a preparation method thereof, a lithium metal battery and an electronic product. Background Art
[0002] Lithium metal batteries have long been widely used in power integration (new energy vehicles), consumer electronics (mobile phones, notebooks, wearable devices), energy storage (5G base stations, smart grids), and in all aspects of life due to their high energy density, long cycle life, fast charging speed, high discharge power, low self-discharge rate, and low memory effect. Lithium metal batteries face many challenges, mainly including the following aspects: ① Growth of lithium dendrites: During the charging and discharging process, lithium metal anodes are prone to the growth of lithium dendrites, which not only affects the cycle stability and life of the battery, but also may penetrate the diaphragm to cause a short circuit, bringing serious safety risks. ② Interface instability between electrolyte and lithium metal anode: The traditional liquid electrolyte has a high reactivity with the lithium metal interface, and it is easy to form an unstable solid electrolyte interface (SEI), which affects the performance and safety of the battery. ③ Decomposition and side reactions of the electrolyte: Similar to liquid lithium metal batteries, the electrolyte is easy to decompose during the charging and discharging process, and side reactions occur with the electrode interface, resulting in gas production, bulging and other problems.
[0003] In order to solve the above problems, gel polymer electrolytes have been extensively studied. However, traditional gel polymer electrolytes still have the problem of slow movement of polymer chain segments, resulting in low ionic conductivity of the electrolyte. It is necessary to further optimize the composition and structure of the gel electrolyte to improve its interface stability and wettability with the lithium metal negative electrode. Summary of the invention
[0004] Based on this, it is necessary to provide a gel polymer electrolyte with good conductivity and stability and a preparation method thereof, a lithium metal battery and an electronic product.
[0005] The present application provides a gel polymer electrolyte, comprising a polymer, an aliphatic dinitrile solvent and a lithium salt in a mass ratio of (0.1-0.5): (0.5-0.9): (0.2-0.4);
[0006] Wherein, the molecular weight of the aliphatic dinitrile solvent is 20 to 200;
[0007] The molecular weight of the polymer is 50,000 to 300,000;
[0008] The polymer includes one or more of polymethyl methacrylate, polybutyl acrylate, polyhydroxyethyl methacrylate and polybutyl methacrylate.
[0009] In one embodiment, the aliphatic dinitrile solvent includes one or more of succinonitrile, glutaronitrile, acetonitrile and adiponitrile.
[0010] In one embodiment, the lithium salt includes one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiSbF6, LiCF3SO3, LiN(SO2CF3)2 (LiTFSI), LiN(SO2C2F5)2 (LiBETI), LiC(SO2CF3)3, LiN(SO2F)2 (LiFAP), LiPO2F2, LiBOB, LiDFOB, LiDFOP, LiFSI and LiPFSI.
[0011] In one embodiment, the gel polymer electrolyte further includes an additive, an initiator and a cross-linking agent; wherein the mass ratio of the polymer, the aliphatic dinitrile solvent, the lithium salt, the additive, the initiator and the cross-linking agent is (0.1:0.5:0.2:0.02:0.004:0.03) to (0.5:0.9:0.4:0.04:0.006:0.05).
[0012] In one embodiment, the additive includes one or more of fluoroethylene carbonate, vinylene carbonate, lithium difluorooxalatoborate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate and propene sultone.
[0013] In one embodiment, the initiator comprises a free radical initiator.
[0014] In one embodiment, the crosslinking agent includes one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate and polyether acrylate.
[0015] The present application also provides a method for preparing the gel polymer electrolyte as described above, comprising the following steps:
[0016] Providing monomers, aliphatic dinitrile solvents and lithium salts, wherein the monomers include one or more of methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and butyl methacrylate;
[0017] The monomer, the aliphatic dinitrile solvent and the lithium salt are mixed in a mass ratio of (0.1-0.5): (0.5-0.9): (0.2-0.4), and the monomer is polymerized to form a polymer, which is then cured to prepare a gel polymer electrolyte.
[0018] Furthermore, the present application also provides a lithium metal battery, comprising a diaphragm, a positive electrode plate, a negative electrode plate and the above-mentioned gel polymer electrolyte, wherein the diaphragm is located between the positive electrode plate and the negative electrode plate, and the positive electrode plate, the negative electrode plate and the diaphragm are placed in the gel polymer electrolyte.
[0019] Furthermore, the present application also provides an electronic product, whose power supply device is the above-mentioned lithium metal battery.
[0020] The gel polymer electrolyte provided by the present application uses a polymer of a specific molecular weight and type to capture aliphatic dinitrile solvent molecules with a molecular weight of 20 to 200 through molecular interactions and improve the solvation structure, thereby preventing the side reaction between lithium metal and aliphatic dinitrile solvents. At the same time, the polymer can capture anions, thereby increasing the number of lithium ion migrations, effectively slowing down the concentration gradient between the negative electrode and the positive electrode, reducing the concentration polarization phenomenon, not only improving the lithium ion conductivity, but also further improving the stability. The battery with the above-mentioned gel polymer electrolyte has good electrochemical performance and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 The figure is a comparison chart of the cycle performance of the lithium cobalt oxide batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0023] Figure 2 This is a comparison chart of the rate performance of lithium cobalt oxide batteries prepared in Example 1, Example 6 and Comparative Example 2;
[0024] Figure 3 It is a comparison chart of the 0.1C and 1C first charge and discharge curves of the lithium cobalt oxide battery prepared in Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0025] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0027] the term:
[0028] The term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions: A, B, and "a combination of A and B".
[0029] In this article, unless otherwise specified, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other expressions that mean "one or more" are also understood in the same way unless otherwise specified.
[0030] In this document, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent technical solutions are related in terms of the content covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0031] Herein, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" item is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist, or means that component X is contained or not contained.
[0032] In this document, the terms "first", "second", "third", "fourth", etc. in "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0033] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0034] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0035] Herein, the term "room temperature" or "normal temperature" generally refers to 4°C to 35°C, for example, 20°C ± 5°C. In some embodiments herein, "room temperature" or "normal temperature" refers to 10°C to 30°C. In some embodiments herein, "room temperature" or "normal temperature" refers to 20°C to 30°C.
[0036] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0037] The present application provides a gel polymer electrolyte, comprising a polymer, an aliphatic dinitrile solvent and a lithium salt in a mass ratio of (0.1-0.5): (0.5-0.9): (0.2-0.4);
[0038] Among them, the molecular weight of aliphatic dinitrile solvents is 20~200;
[0039] The molecular weight of the polymer is 50,000~300,000;
[0040] The polymer includes one or more of polymethyl methacrylate, polybutyl acrylate, polyhydroxyethyl methacrylate, and polybutyl methacrylate.
[0041] It can be understood that the gel polymer electrolyte is specifically a polymer forming a gel skeleton, and a solvent and a lithium salt are filled in the skeleton.
[0042] The gel polymer electrolyte provided by the present application uses polymers to capture aliphatic dinitrile solvent molecules and improve the solvation structure through molecular interactions, thereby preventing side reactions between lithium metal and aliphatic dinitrile solvents. At the same time, the polymer can capture anions, thereby increasing the number of lithium ion migrations, effectively slowing down the concentration gradient between the negative electrode and the positive electrode, reducing the concentration polarization phenomenon, not only improving the lithium ion conductivity, but also further improving the stability. The battery with the above-mentioned gel polymer electrolyte has good electrochemical performance and safety.
[0043] Further, the molecular weight of the aliphatic dinitrile solvent is 40-110. Specifically, the molecular weight of the aliphatic dinitrile solvent can be, but is not limited to, 40, 50, 60, 70, 80, 90, 100 or 110.
[0044] In a specific example, the aliphatic dinitrile solvent includes one or more of succinonitrile, glutaronitrile, acetonitrile and adiponitrile.
[0045] In a specific example, the lithium salt includes one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiSbF6, LiCF3SO3, LiN(SO2CF3)2 (LiTFSI), LiN(SO2C2F5)2 (LiBETI), LiC(SO2CF3)3, LiN(SO2F)2 (LiFAP), LiPO2F2, LiBOB, LiDFOB, LiDFOP, LiFSI and LiPFSI.
[0046] In a specific example, the gel polymer electrolyte further includes an additive, an initiator and a cross-linking agent; wherein the mass ratio of the polymer, the aliphatic dinitrile solvent, the lithium salt, the additive, the initiator and the cross-linking agent is (0.1:0.5:0.2:0.02:0.004:0.03) to (0.5:0.9:0.4:0.04:0.006:0.05).
[0047] It can be understood that the mass ratio of polymer, aliphatic dinitrile solvent, lithium salt, additive, initiator and cross-linking agent is (0.1~0.5):(0.5~0.9):(0.2~0.4):(0.02~0.04):(0.004~0.006):(0.03~0.05).
[0048] In a specific example, the mass ratio of the polymer to the cross-linking agent is (0.1~0.5):(0.03~0.05).
[0049] In a specific example, the additive includes one or more of fluoroethylene carbonate, vinylene carbonate, lithium difluorooxalatoborate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, and propene sultone.
[0050] In a specific example, the initiator includes a free radical initiator. Specifically, the initiator may include, but is not limited to, one or more of azobisisobutyronitrile (AIBN), azobismethylpropionitrile (AMBN), azobisvinylpropionitrile (ADVN), azobisisopropionitrile (ACVA), benzoyl peroxide (BPO), and acetyl peroxide (AAPH).
[0051] In a specific example, the crosslinking agent includes one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, and polyether acrylate.
[0052] The present application also provides a method for preparing the gel polymer electrolyte as described above, comprising the following steps:
[0053] Providing monomers, aliphatic dinitrile solvents and lithium salts, wherein the monomers include one or more of methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and butyl methacrylate;
[0054] A mixed monomer, an aliphatic dinitrile solvent and a lithium salt in a mass ratio of (0.1-0.5): (0.5-0.9): (0.2-0.4) are prepared, the monomer is polymerized to form a polymer, and the polymer is solidified to prepare a gel polymer electrolyte.
[0055] In a specific example, a first precursor and a second precursor are provided. Specifically, the first precursor includes a monomer, an initiator, a cross-linking agent and a first portion of a lithium salt, and the second precursor includes an aliphatic dinitrile solvent, an additive and a second portion of a lithium salt.
[0056] In a specific example, the curing method includes but is not limited to in-situ curing by thermal initiation or ultraviolet light initiation, and the curing time is 2 hours to 48 hours. Specifically, the thermal initiation temperature is 20° C. to 100° C.
[0057] Furthermore, the present application also provides a lithium metal battery, comprising a diaphragm, a positive electrode plate, a negative electrode plate and the above-mentioned gel polymer electrolyte, wherein the diaphragm is located between the positive electrode plate and the negative electrode plate, and the positive electrode plate, the negative electrode plate and the diaphragm are placed in the gel polymer electrolyte.
[0058] In a specific example, the material of the negative electrode plate may include, but is not limited to, one or more of metallic lithium, graphite, soft carbon, hard carbon, silicon-carbon composite materials, silicon oxide materials, nano-silicon materials, and silicon-oxygen materials.
[0059] It is understandable that the material of the negative electrode plate may also include one or both of a conductive agent and a binder. The conductive agent may include, but is not limited to, one or more of conductive carbon black, graphene, and conductive polymers. The binder may include, but is not limited to, one or more of polyvinylidene fluoride (PVDF), polyacrylate (PAA), carboxymethyl cellulose (CMC), and polyvinyl alcohol (PVA).
[0060] In a specific example, the material of the positive electrode plate may include, but is not limited to, a ternary layered Li(NixCoyMnz)O2 material (x+y+z=1), a lithium-rich manganese-based material, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, and one or more of the above materials independently modified by doping elements.
[0061] Furthermore, the doping element may be, but is not limited to, one or more of Al, Zr, Mg, Ti, Si and F.
[0062] In a specific example, the separator may be, but is not limited to, one or more of glass fiber, polypropylene microporous membrane (PP), and polyethylene microporous membrane (PE).
[0063] Furthermore, the present application also provides an electronic product, whose power supply device is the above-mentioned lithium metal battery.
[0064] The present application is further described in detail below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance given in the present application, and can also be based on the experimental manuals or conventional conditions in the art, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0065] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed. "Normal temperature" refers to 25°C; "normal pressure" refers to 100KPa or 101KPa.
[0066] Example 1
[0067] 1) Preparation of electrolyte: First, mix a lithium salt with a mass fraction of 2.5% in a reagent bottle containing butyl acrylate (BA), and then add azoisobutyronitrile (AIBN) as an initiator and polyethylene glycol dimethacrylate (PEGDA) as a cross-linking agent to obtain a clear and transparent solution.
[0068] 2) Preparation of gel electrolyte precursor: In another reagent bottle, dissolve the same mass fraction of lithium salt in adiponitrile (ADN) solution, then add fluoroethylene carbonate (FEC) and heat at 60°C until completely dissolved. Subsequently, the liquids in the two bottles are mixed at different concentrations to form a quasi-solid electrolyte precursor.
[0069] 3) Preparation of positive electrode materials: 80% of positive electrode materials (NCM811 / NCM90 and lithium cobalt oxide LCO), 10% SuperP and 10% polyvinylidene fluoride (PVDF) were uniformly dispersed in N-methylpyrrolidine (NMP). The mixture was coated on aluminum foil and vacuum dried at 100 °C for 12 hours. The area loading of the positive electrode was about 8 mg cm -2 , the electrode area is about 12cm 2 .
[0070] 4) Preparation of negative electrode materials: Ultrathin lithium metal sheet (20 μm) was used as the negative electrode.
[0071] 5) Preparation of battery cells: Place a 20μm thick glass fiber as a separator between the positive plate and the negative plate, then wind the sandwich structure consisting of the positive plate, negative plate and separator, flatten the wound body and put it into an aluminum-plastic film, lead out the positive and negative lead wires respectively, and then hot-press and seal the aluminum-plastic film to obtain a battery cell to be injected with liquid.
[0072] 6) Battery assembly: In a glove box with a dew point controlled below 40°C, inject the above-prepared gel electrolyte precursor into the battery cell, with an injection volume of 1 ml. After the precursor fully infiltrates the battery cell, clamp the soft-pack battery cell with a clamp, then place it in an oven at 60°C and let it stand for 8 hours to polymerize, and obtain a fully cured gel battery.
[0073] 7) Battery formation: First charge at a constant current of 0.05C for 180 minutes, then charge at a constant current of 0.1C for 180 minutes, leave it for 24 hours, seal it and shape it, then further charge it at a constant current of 0.2C to 4.6V, leave it at room temperature for 24 hours, and then discharge it at a constant current of 0.2C to 2.9V.
[0074] The formulas of the gel electrolytes of Examples 1-5 are shown in the following table, and the rest are the same as those of Example 1.
[0075]
[0076] Example 6
[0077] The difference from Example 1 is that adiponitrile is replaced by succinonitrile (SN), and other parameters remain unchanged.
[0078] Example 7
[0079] The difference from Example 1 is that adiponitrile is replaced by glutaronitrile (GLN), and other parameters remain unchanged.
[0080] Example 8
[0081] The difference from Example 1 is that adiponitrile is replaced by acetonitrile (AN), and other parameters remain unchanged.
[0082] Comparative Example 1
[0083] The difference from Example 1 is that butyl acrylate (BA) is not added and the amount of adiponitrile (ADN) added is 1 g.
[0084] Comparative Example 2
[0085] The difference from Example 1 is that butyl acrylate (BA) is not added, and the same mass of adiponitrile (ADN) is replaced by ethyl methyl carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:7.
[0086] Comparative Example 3
[0087] The difference from Example 1 is that the same mass of adiponitrile (ADN) is replaced by ethyl methyl carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:7.
[0088] Comparative Example 4
[0089] The difference from Example 2 is that the same mass of adiponitrile (ADN) is replaced by ethyl methyl carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:7.
[0090] Comparative Example 5
[0091] The difference from Example 1 is that the same mass of adiponitrile (ADN) is replaced by ethyl methyl carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 3:7.
[0092] Comparative Example 6
[0093] The difference from Example 1 is that the same mass of adiponitrile (ADN) is replaced by polycarbonate (PC) and ethyl methyl carbonate (EMC) in a mass ratio of 3:7.
[0094] Comparative Example 7
[0095] The difference from Example 1 is that the same mass of adiponitrile (ADN) is replaced by diphenylmethane diisocyanate (MDI), and the other components remain unchanged.
[0096] Detection methods and result characterization
[0097] First coulombic efficiency: In the battery formation step, the charge capacity Q1 is recorded, the discharge capacity is Q2, and the first coulombic efficiency is expressed as Q2 / Q1. This performance parameter reflects the degree of side reactions between the electrolyte and the electrode during the first charge of the battery.
[0098] Capacity retention rate after 300 cycles: At 30°C, charge to 4.6 V at 1 C constant current, then discharge to 2.9 V at 1 C constant current, and repeat this cycle for 300 cycles. Record the discharge capacity at the 300th cycle, and calculate the capacity retention rate as follows:
[0099] Capacity retention rate = (discharge capacity at the 300th week / initial nominal capacity of the battery) × 100%. Here, the initial nominal capacity of the battery is 200 mAh g -1 .
[0100] 2C / 3C capacity utilization (mAh / g) test:
[0101] At 30°C, the battery was charged to 4.6 V at a constant current of 1 C, and then discharged to 2.9 V at a constant current of 2C / 3C. The battery discharge capacity Q was recorded and divided by the mass of all positive electrode material active substances to obtain the battery specific capacity at 2C / 3C.
[0102] Lithium metal corrosion degree:
[0103] At 30°C, the battery was charged to 4.6 V at a constant current of 1 C and transferred to a glove box with a pure argon atmosphere for full-charge disassembly. The fully charged graphite negative electrode was photographed and its surface color and morphology were observed.
[0104] Uncorroded: The lithium metal surface retains its original matte white color with no noticeable color changes or spots. The surface structure is intact with no cracks, dents or other forms of damage.
[0105] Slight corrosion: There are a few black spots on the lithium metal surface, but most areas still show the initial matte white. The surface structure is basically intact, without serious structural damage.
[0106] Severe corrosion: Black spots appear over most of the lithium metal surface, and the matte white area is significantly reduced. There is significant damage to the surface structure, such as deep cracks and severe pitting.
[0107] Results Analysis
[0108] This application uses a series of experiments to explore the performance of polybutyl acrylate (PBA) and small molecule aliphatic dinitrile solvents such as adiponitrile (ADN) as gel polymer electrolytes in lithium metal batteries. The above experimental results show that the introduction of PBA in the design of gel polymer electrolytes has a significant impact on improving battery performance and safety.
[0109] The battery performances of Examples 1-8 and Comparative Examples 1-6 are summarized in the following table.
[0110]
[0111] In the present embodiment, by using a specific polymer such as PBA as the polymer skeleton in the quasi-solid electrolyte and combining it with a small molecule aliphatic dinitrile solvent, the high binding energy between lithium ions and the small molecule aliphatic dinitrile solvent significantly affects the Li + Specifically, in the above embodiment of the present application, the addition of PBA can effectively capture the aliphatic dinitrile solvent or the Li + In the solvation structure of + This not only prevents the side reaction of lithium with aliphatic dinitrile solvent solutions, but also significantly improves the mobility of lithium ions and reduces the interfacial impedance, thereby achieving better electrochemical performance and safety in high energy density batteries.
[0112] like Figure 1 , Figure 2 , Figure 3 The experimental results in the table above further show that the addition of PBA can also effectively capture TFSI - Anions increase the number of lithium ion migration, thereby reducing the concentration gradient between the negative and positive electrodes of the battery, significantly improving the battery performance. In addition, the ratio of polymer to aliphatic dinitrile solvent has a decisive influence on battery performance. When the PBA content is too high (Example 2 and Example 3), although it can effectively capture ADN and prevent the side reaction of lithium metal and solvent, the conductivity of the electrolyte is reduced, resulting in an increase in battery impedance and limited charge and discharge performance; when the PBA content is too low (Example 5 and Example 6), the PBA formed after polymerization does not participate enough in Li + In the solvated structure, it competes with ADN for Li + Coordination causes side reactions with the lithium negative electrode, so the first coulombic efficiency is low, the cycle performance is reduced, and the 2C rate discharge capacity is relatively insufficient.
[0113] When BA and ADN are used in combination according to the ratio in Example 1, the battery exhibits the best comprehensive performance. It not only exhibits excellent cycle stability, but also achieves higher rate charge and discharge performance and lower lithium metal corrosion, indicating that the electrolyte system under this ratio can effectively prevent the side reaction of lithium metal while maintaining good conductivity and low interface impedance.
[0114] Through observation of the needle puncture safety experiment of Examples 1-8, even under extreme conditions, the battery exhibits good safety performance, does not catch fire, explode or smoke, and only the temperature rises, which further proves the superiority and potential application value of the electrolyte system of the present application.
[0115] Through Examples 1, 6, 7 and 8, it can be found that when BA and nitrile solvents are added in a certain ratio, changing the nitrile solvent component in the electrolyte solvent composition (changing ADN with SN, GLN or AN) will also affect the battery performance to a certain extent. + The strong binding energy and mechanical properties of ADN & PBA gel cannot inhibit the precipitation of lithium dendrites during battery cycling, resulting in poor battery cycle stability. Comparative Examples 2 to 6 try to use traditional commercial electrolyte solvents with polymer skeleton PBA, and the 2C rate capacity is seriously insufficient, only 59.4 mAh / g. This is due to the lower dielectric constant and weaker lithium salt dissociation ability of carbonate. At the same time, due to the lack of ultra-low viscosity, it is not enough to form a sufficient solid-solid interface during the battery infiltration and curing process, resulting in a large overall internal resistance, so the excellent rate discharge performance in the embodiment cannot be achieved.
[0116] However, the battery performance of Comparative Example 7, which uses a combination of other monomers and aliphatic dinitrile solvents, is greatly reduced. The corrosion of the aliphatic dinitrile solvent on the lithium metal negative electrode is not effectively inhibited, and there is no obvious improvement on the intrinsic conductivity and polarization problems of the solid-state battery.
[0117] In summary, through the combination of monomers and aliphatic dinitrile solvents in appropriate proportions, the aliphatic dinitrile solvents formed can inhibit the corrosion of aliphatic dinitrile solvents to the lithium metal negative electrode, and can fully alleviate the intrinsic conductivity and polarization problems of solid-state batteries, which not only improves the ionic conductivity and lithium ion migration coefficient of lithium metal batteries. It also improves the stability of the electrolyte and electrode interface. This lays a solid foundation for the development of new high-energy density and high-safety lithium metal batteries. The electrolyte of this application provides a new way for the development of future lithium battery technology, and is expected to be widely used in fields such as electric vehicles and portable electronic devices.
[0118] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0119] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the specification and drawings may be used to interpret the scope of the claims.
Claims
1. A gel polymer electrolyte, characterized in that: It includes a polymer, an aliphatic dinitrile solvent and a lithium salt in a mass ratio of (0.1-0.5): (0.5-0.9): (0.2-0.4); Wherein, the molecular weight of the aliphatic dinitrile solvent is 20 to 200; The molecular weight of the polymer is 50,000 to 300,000; The polymer includes one or more of polymethyl methacrylate, polybutyl acrylate, polyhydroxyethyl methacrylate and polybutyl methacrylate.
2. The gel polymer electrolyte according to claim 1, characterized in that The aliphatic dinitrile solvent includes one or more of succinonitrile, glutaronitrile, acetonitrile and adiponitrile.
3. The gel polymer electrolyte according to claim 1, characterized in that The lithium salt includes one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiSbF6, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiPO2F2, LiBOB, LiDFOB, LiDFOP, LiFSI and LiPFSI.
4. The gel polymer electrolyte according to any one of claims 1 to 3, characterized in that The gel polymer electrolyte also includes an additive, an initiator and a cross-linking agent; wherein the mass ratio of the polymer, the aliphatic dinitrile solvent, the lithium salt, the additive, the initiator and the cross-linking agent is (0.1:0.5:0.2:0.02:0.004:0.03) to (0.5:0.9:0.4:0.04:0.006:0.05).
5. The gel polymer electrolyte according to claim 4, characterized in that The additive includes one or more of fluoroethylene carbonate, vinylene carbonate, lithium difluorooxalatoborate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate and propene sultone.
6. The gel polymer electrolyte according to claim 4, characterized in that The initiator includes a free radical initiator.
7. The gel polymer electrolyte according to claim 4, characterized in that The crosslinking agent includes one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate and polyether acrylate.
8. A method for preparing a gel polymer electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: Providing monomers, aliphatic dinitrile solvents and lithium salts, wherein the monomers include one or more of methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and butyl methacrylate; The monomer, the aliphatic dinitrile solvent and the lithium salt are mixed in a mass ratio of (0.1-0.5): (0.5-0.9): (0.2-0.4), and the monomer is polymerized to form a polymer, which is then cured to prepare a gel polymer electrolyte.
9. A lithium metal battery, characterized in that: Contains a separator, a positive electrode sheet, a negative electrode sheet and a gel polymer electrolyte as described in any one of claims 1 to 7, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet, the negative electrode sheet and the separator are placed in the gel polymer electrolyte.
10. An electronic product, characterized in that: The power supply device is the lithium metal battery as described in claim 9.
